PEMELIHARAAN LARVA IKAN KATUNG (Pristolepis grooti Bleeker) DENGAN PEMBERIAN PAKAN AWAL BERBEDA - Hamdan Alawi; Netti Ariyani; Nur Asiah (Universitas Sriwijaya, 2014)
ABSTRACT The Indonesian Leaffish, Pristolepis grooti is one of endangered species found in some river system in Indonesia. The demanded and good culture candidate species for which the development of larval raring techniques are needed for large scale. A study was conducted to assess the effects of different type of feeds on growth and survival rate of the larva for 35 days rearing period. The experiment was designed on completely randomized design (CRD) with 4 treatments, each with 3 replications. Four different feeds were tested, viz. AR (Artemia nauplii), TB (tubificid worms), WF (Water Flea, Daphnia and Moina) and BE (Boiled chicken egg yolk). Induced bred larvae (10-day old) were reared in 20 liters glass aquarium with a recirculation water system During the experimental period the larvae were fed to satiation three times a day. The water quality variables such as temperature, dissolved oxygen (DO), pH, free ammonia, were found within acceptable limit of larval rearing. The larvae fed tubificid worms had significantly highest (P<0.05) growth (percent length gain (423.3±37.3), percent weight gain (13905.5±567.6), specific growth rate (14.1±0.1) and survival (63.3±16.1) followed by Artemia nauplii and water Flea and boiled chickedn egg yolk. Therefore, tubificid worms may be suggested for feeding Indonesian leaffish larvae up to stockable size. Keywords: Pristolepis grootii, feed type, growth and survival, larval rearing